1984
DOI: 10.1111/j.1748-1716.1984.tb07422.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of some α‐adrenoceptor stimulating and blocking agents on the salivary amylase secretion in the rabbit

Abstract: In rabbits under urethane anaesthesia parotid secretion of fluid and amylase in response to electrical stimulation of the sympathetic and parasympathetic nerves was measured before and after injections of various agents acting on alpha-adrenoceptors. Amylase secretion in response to sympathetic nerve stimulation at 0.5 and 1 Hz was markedly reduced by clonidine, 0.5-30 micrograms/kg, in a dose related manner. The effect was not due to an altered responsiveness of the gland, since isoprenaline still caused a la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

1985
1985
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 40 publications
1
3
0
Order By: Relevance
“…Furthermore, the inhibitory effect of the betai-adrenergic antagonist, atenolol, and the slightly stimulatory effect of the beta2-adrenergic agonist, salbutamol, sug gests that secretion of salivary amylase is predominantly mediated by activation of beta i-adrenergic receptors. These results are in agreement with previous in vivo studies in rabbits demonstrating that salivary secretion of amylase was abolished by betai-adrener gic antagonists as well as clonidine, an alphaadrenergic antagonist [5]. This mode of stim ulation differs from other substances se creted by the salivary glands.…”
Section: Discussionsupporting
confidence: 83%
“…Furthermore, the inhibitory effect of the betai-adrenergic antagonist, atenolol, and the slightly stimulatory effect of the beta2-adrenergic agonist, salbutamol, sug gests that secretion of salivary amylase is predominantly mediated by activation of beta i-adrenergic receptors. These results are in agreement with previous in vivo studies in rabbits demonstrating that salivary secretion of amylase was abolished by betai-adrener gic antagonists as well as clonidine, an alphaadrenergic antagonist [5]. This mode of stim ulation differs from other substances se creted by the salivary glands.…”
Section: Discussionsupporting
confidence: 83%
“…In Study 4, rats received daily intraperitoneal injections of clonidine (at2-adrenergic agonist, 30 ,xg/kg, n = 8; Gjorstrup, 1984), yohimbine (a2-adrenergic antagonist, 1 mg/kg, n = 8; Gjorstrup, 1984), or saline (control, n = 8) for a period of one week. Statistical analysis of the data was performed by means of a t test (Bruning and Kintz, 1977) or analysis of variance (SPSS, Nie et al, 1975).…”
Section: Methodsmentioning
confidence: 99%
“…Our physiological and biochemical observations indicate TEN may partially act by producing an increase in α2 adrenergic receptor activity to inhibit NE levels through known negative feedback mechanisms. Clonidine, an α2 adrenoceptor agonist, has been shown to block sAA secretion triggered by sympathetic fiber stimulation 61 . Similarly, we observed that TEN significantly attenuated the levels of sAA following stress induction as discussed above ( Fig.…”
Section: Discussionmentioning
confidence: 99%